2018
DOI: 10.1002/advs.201800873
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Mitophagy to Cell‐Mediated Mineralization: Revisiting a 50‐Year‐Old Conundrum

Abstract: Biomineralization in vertebrates is initiated via amorphous calcium phosphate (ACP) precursors. These precursors infiltrate the extracellular collagen matrix where they undergo phase transformation into intrafibrillar carbonated apatite. Although it is well established that ACP precursors are released from intracellular vesicles through exocytosis, an unsolved enigma in this cell‐mediated mineralization process is how ACP precursors, initially produced in the mitochondria, are translocated to the intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 66 publications
(91 reference statements)
1
54
0
Order By: Relevance
“…Also, the process of mitophagy was proven to participate in the cell-mediated biomineralization process. To be specific, the amorphous calcium phosphate, which was the precursor in biomineralization, could trigger mitophagy to transport intracellularly via the autophagosome and released to the extracellular matrix via exocytosis ( Pei et al, 2018 ). In this study, with the relative expression of mitophagy-related gene upregulated at 5 days, the osteogenesis-related gene expression of SLM-CO group was promoted, which was consistent with other relevant studies ( Hyzy et al, 2016 ; H. Wang et al, 2018 ; Yu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the process of mitophagy was proven to participate in the cell-mediated biomineralization process. To be specific, the amorphous calcium phosphate, which was the precursor in biomineralization, could trigger mitophagy to transport intracellularly via the autophagosome and released to the extracellular matrix via exocytosis ( Pei et al, 2018 ). In this study, with the relative expression of mitophagy-related gene upregulated at 5 days, the osteogenesis-related gene expression of SLM-CO group was promoted, which was consistent with other relevant studies ( Hyzy et al, 2016 ; H. Wang et al, 2018 ; Yu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…markedly impedes osteoblast survival. Recent studies have suggested that mitophagy is important in regulating osteoblast survival and function (Pei et al, 2018a;Zhao et al, 2020). Nevertheless, the involvement of osteoblast mitophagy in the pathogenesis of GIOP is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that GC excess interrupts mitochondrial function and prolonged exposure deteriorates mitochondrial integrity leading to release of pro-apoptotic proteins, reactive oxygen species (ROS) accumulation, and ineffective generation of ATP that markedly impedes osteoblast survival. Recent studies have suggested that mitophagy is important in regulating osteoblast survival and function ( Pei et al., 2018a ; Zhao et al., 2020 ). Nevertheless, the involvement of osteoblast mitophagy in the pathogenesis of GIOP is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, knock down of PINK1 in human dental pulp stem cells (hDPSCs) results in impaired osteogenesis (Pei et al, 2018 ). Possibly, mitophagy is underpinning dual roles within VSMCs by (i) contributing to bone formation via exocytosis of Ca and Pi-filled mitochondrial-derived vesicles packed in autolysosomes to the extracellular matrix and (ii) clearing dysfunctional mitochondria within calcified VSMCs.…”
Section: Mitochondrial Quality Control In Vascular Calcificationmentioning
confidence: 99%